Wild hogs in the water: Contested infrastructural ecologies of reservoir storage in texas - RANDLE, Sayd (Institutional Knowledge at Singapore Management University, 2024)
Reservoirs are developed to store water in reserve for future use. But once built, reservoir sites inevitably hold more than just water, often serving as a key habitat for a range of species. This paper examines how one such animal has transformed water storage facilities and nearby landscapes into contested ground in urbanising areas of Texas, USA. Living around the reservoirs, feral hogs complicate the process of urbanisation by degrading the stockpiled water and infrastructure at the storage sites themselves and by damaging private property throughout the surrounding landscape. Tracking local efforts to manage the hogs, the case study illustrates the spatially extensive stakes of such porous infrastructural ecologies of storage, particularly their role in mediating the ongoing process of the urbanisation of nature.